Penerapan Model PBL (Problem Based Learning) Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas V Di SDN 19 Mataram Tahun 2022/2023 - Lestari, Ines Maharani; Tahir, Muhammad; Rizki, Irma Suyatna (Journal of Science Instruction and Technology, 2023)
This study aims to enhance learning motivation by applying PBL (Problem Based Learning) model to the students of Class V SDN 19 Matar in the academic year 2022/2023. This type of study is a classroom study. Data collection methods use questionnaires, documentation and tests. Types of data used: qualitative data and quantitative data. The subjects of the study were students of class V SDN 19 Mataram, a total of 21 students. The results of the study showed that there was an increase in the percentage of students' educational motivation, namely, before the cycle, this percentage was 64% with a poor category (K), then in the first cycle it increased to 75% with a sufficient one. category (C) and increased to 80% in the second cycle with good category (B), which means that the PBL (Problem Based Learning) model is very effective in increasing the learning motivation of students of class V SDN 19 Mataram 2022. /2023 academic year.